Understanding the Aroma Profiles of Hui Li Red Sichuan Pepper (Zanthoxylum bungeanum Maxim) Across Harvesting Periods Using Sensory Evaluation, E-Nose and GC-IMS Techniques - Lian He; Sook Wah Chan; Sze Ying Leong; Mingyi Guo; Zhiyong Hou; Xiangbo Xu; Nallammai Singaram; Dan Lin; Xing Qiao; Lin Wang; Huachang Wu; Zongyuan Lu (Foods)
This study investigated aroma changes in Hui Li red Sichuan pepper across five different harvesting times within their typical optimum period based on 24 traditional solar terms, employing sensory evaluation, electronic nose (E-nose), gas chromatography-ion mobility spectrometry (GC-IMS) combined with relative odour activity value (ROAV) and partial least squares discriminant analysis (PLS-DA). Sensory analysis indicated that peppers were characterised by green, citrus, minty, sweet, woody, and peppery numbing aroma attributes. E-nose revealed the greatest aroma difference in peppers occurred between the early and late optimum harvest stages. GC-IMS identified 71 volatile compounds, with esters being the most abundant. Six key compounds identified were crucial for distinguishing peppers harvested at different times. Findings provided a valuable contribution to decide the optimal harvest window for Hui Li red Sichuan peppers, maximising their applications in the seasoning industry.